Monitoring Goat Feeders Using IoT (Internet of Things) Technology - Muhammad Syahputra Novelan (SEAN Institute, 2023)
Goat confine cultivating as of now has awesome potential. While running a goat ranch, mistakes frequently happen in booking animal feed and estimating the heaviness of feed to give programmed feed progressively as per the predefined time.